2005
DOI: 10.1128/iai.73.4.2094-2100.2005
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejuni-Induced Cytokine Responses in Avian Cells

Abstract: Campylobacter jejuni is a major cause of human inflammatory enteritis. During the course of human disease numerous proinflammatory cytokines are produced. Little is known, however, about the cytokine responses produced during the interaction of this bacterium with the avian host. Campylobacter has been considered a commensal of the avian host. Any differences in innate responses to this pathogen between the human and avian hosts should lead to a greater understanding of the disease process in humans. We have d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 45 publications
2
62
0
Order By: Relevance
“…Although immature birds challenged by large C. jejuni inocula may get diarrhoea and some reports allude to a form of vibrionic hepatitis, there is no evidence that naturally acquired C. jejuni causes infection in avian intestinal epithelium cells (Newell, 2000;Skirrow, 1994). Recently, Smith et al (2005) used an avian kidney cell model of Campylobacter infection and showed adherence to and invasion of these cells but the interaction of Campylobacter with avian intestinal cells has never been studied directly. In this study we have developed a primary cell model of intestinal campylobacteriosis to investigate the host-specific tropism of these organisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although immature birds challenged by large C. jejuni inocula may get diarrhoea and some reports allude to a form of vibrionic hepatitis, there is no evidence that naturally acquired C. jejuni causes infection in avian intestinal epithelium cells (Newell, 2000;Skirrow, 1994). Recently, Smith et al (2005) used an avian kidney cell model of Campylobacter infection and showed adherence to and invasion of these cells but the interaction of Campylobacter with avian intestinal cells has never been studied directly. In this study we have developed a primary cell model of intestinal campylobacteriosis to investigate the host-specific tropism of these organisms.…”
Section: Discussionmentioning
confidence: 99%
“…This would have substantial implications for furthering our understanding of the ecology of the intestinal tract. (Smith et al, 2005). These studies raise the possibility that the avian immune system could influence Campylobacter infectivity in vivo.…”
Section: Meinersmannmentioning
confidence: 99%
“…Primers and probes (Table II) were designed as described (40,41) or using the Primer Express software (Applied Biosystems). Probes (Isogen Life Science) were labeled with the reporter dye carboxyfluorescein (FAM) and the quencher tetramethyl-6-carboxyrhodamine (TAMRA).…”
Section: Rna Isolation and Quantitative Rt-pcrmentioning
confidence: 99%
“…with intestinal epithelial cells result in the production of cytokines, which are regulators of host responses to infection, and which have important roles in the pathogenesis of infectious diseases. [19][20][21] Cytokines are produced by immune cells, and according to their function, they are divided into the pro-inflammatory cytokines, such as interleukin (IL)-1, IL-2, IL-6, IL-8, IL-12, IL-17 and IL-18, tumor necrosis factor (TNF)-a, and interferon (IFN)-g, and the antiinflammatory cytokines, such as IL-4, IL-10 and tumor growth factor-b. 2,22 Both pro-inflammatory and anti-inflammatory cytokines are induced during Campylobacter spp infection, and it is important to determine whether the immune system is successful in providing protection against these specific pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…5 Some cytokines can be produced in excess, and thus these might contribute strongly to disease pathology. 19 Indeed, it has been reported that macrophages produce IL-1a, IL-1b, IL-6, IL-8 and TNF-a when infected with Campylobacter spp.. 23 However, the pathogenesis of C. coli infection is still poorly understood, which is mainly a consequence of the lack of a suitable animal model that can be used to mimic the course of infection in human. 24 We thus monitored the stability of the virulence and toxin genes (i.e., cadF, virB11, cdtB, cdtC, ceuE) by comparing the sequence data of C. coli 26536 before and after transmission through the host, and their colonisation and cytokine induction in a murine model.…”
Section: Introductionmentioning
confidence: 99%